Factors Influencing Equity Financing within Government Entities in South Africa - Ntuli, Sizwe Perfect; Nzuza, Zwelihle Wiseman; Mbambo, Mzwandile Atkins (International Journal of Economics and Financial Issues, 2024)
Equity financing theorsuggests that firms favour equity financing over debt to mitigate potential external risks and reduce exposure to external scrutiny. The aim of this study is to determine the extent to which various factors influence equity financing decisions within South African government entities. This study investigates the critical factors influencing equity financing decisions within government entities in South Africa. Employing Stata for data analysis, the research utilizes a cross-sectional, quantitative methodology supplemented by questionnaire-based data collection from 51 respondents. The application of Panels corrected standard errors (PCSEs) regression reveals a positive and significant relationship between risk appetite of the company (RAF) and company size (SIZE) with equity financing evidenced by P = 0.000 and 0.037, respectively. The links between reliance on internal funds (RIF) and equity financing is positive and slightly significant at 0.051 level. Based on these results, it is recommended that government entities assess their risk appetite and internal financial resources carefully when considering equity financing, ensuring alignment with strategic objectives and market conditions.